2015
DOI: 10.1016/j.stemcr.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors

Abstract: SummaryHuman pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 15 publications
2
59
2
Order By: Relevance
“…It is now possible to differentiate iPSCs into many defined types of neurons, e.g., nociceptors, cortical neurons, and MNs although a limitation is that typically they remain immature. For pain, the capacity to generate human nociceptors from stem cells is certainly most promising (Chambers et al, 2012;Eberhardt et al, 2015;Wainger et al, 2015), especially for studying channelopathies like those arising from Nav1.7 mutations (Yang et al, 2018) where the hyperexcitability phenotype is easy to capture either electrophysiologically or with calcium reporter readouts. More complex three-dimensional multicell organoids for modeling cortex (Madhavan et al, 2018;Sloan et al, 2018) and skin (Lee et al, 2018a) are being developed and offer exciting new ways to study complex non-cell-autonomous phenotypes.…”
Section: Patient-derived Neurons As Pain Biomarkersmentioning
confidence: 99%
“…It is now possible to differentiate iPSCs into many defined types of neurons, e.g., nociceptors, cortical neurons, and MNs although a limitation is that typically they remain immature. For pain, the capacity to generate human nociceptors from stem cells is certainly most promising (Chambers et al, 2012;Eberhardt et al, 2015;Wainger et al, 2015), especially for studying channelopathies like those arising from Nav1.7 mutations (Yang et al, 2018) where the hyperexcitability phenotype is easy to capture either electrophysiologically or with calcium reporter readouts. More complex three-dimensional multicell organoids for modeling cortex (Madhavan et al, 2018;Sloan et al, 2018) and skin (Lee et al, 2018a) are being developed and offer exciting new ways to study complex non-cell-autonomous phenotypes.…”
Section: Patient-derived Neurons As Pain Biomarkersmentioning
confidence: 99%
“…Nevertheless, although most neurons exhibited those markers, few showed important functional readouts, such as TRPV1 activation, as only about 1-2% of the cells responded to capsaicin. Other studies were able to demonstrate the expression of canonical peripheral markers, such as BRN3A, peripherin and b-Tubulin III, in sensory neurons derived from hiPSCs, but evidence of specific functional activity was still missing (Menendez et al, 2013, Young et al, 2014, Blanchard et al, 2015, Eberhardt et al, 2015. Young et al (2014) reported measuring TRPV1 activity induced by capsaicin, but only after 6 weeks in medium containing growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Literature analysis reveals the efforts made by several groups to develop more efficient and costeffective protocols for obtaining functional peripheral neurons from human induced pluripotency stem cells (Menendez et al, 2013, Young et al, 2014Blanchard et al, 2015, Eberhardt et al, 2015. However, none of these studies have shown results with human cells or investigated the role of the interaction between human epidermal keratinocytes and the transcriptional profile of mature neurons in the presence of factors released by these cells.…”
Section: Introductionmentioning
confidence: 99%
“…A follow‐up study using electrophysiology techniques later showed that these cells expressed functional ion channels that have been implicated in the pathophysiology of pain and sensory disorders (including HCN1, KCNQ2/3 and GABA A R) . This protocol, amongst others, has subsequently been used to screen for neurotoxic agents and therapeutic drugs to block hyperexcitability of these known targets associated with pain .…”
Section: Stem Cellsmentioning
confidence: 99%